Skinddragter online : = Skin clothing online - Kulturhistorisk museum; Nationalmuseet; Nunatta katersugaasivia (2013)
Here you will find unique, high-resolution, 360 degree rotation photos and detailed information about the National Museum of Denmark’s and the National Museum of Greenland's collections of fur clothing from indigenous peoples in Greenland, North America, Siberia and North Scandinavia from 2500 BC to the present day